Abrupt Pressure Delivery - Samir B. Pancholy, MD; Sanjay Shah, MD, DM; Aman T. Patel, MD, DM; Tejas M. Patel, MD, DM (JACC: Case Reports)
A 71-year-old man with acute coronary syndrome was found to have multiple severe calcified stenoses in the dominant left circumflex coronary artery. After lesion preparation, the distal lesion was stented. A stent was advanced in the proximal lesion and inflated, but during the deployment inflation, the stent balloon ruptured after expansion of the proximal portion of the stent. The distal portion of the stent was unexpanded and bound to the stent balloon. Conventional techniques were used to remove the ruptured balloon without success and led to longitudinal stent deformation. A novel method to deliver abrupt pressure to the ruptured balloon was used, with successful disengagement of the ruptured stent balloon from the partially inflated stent and successful withdrawal. The deformed stent was successfully expanded with subsequent restenting. This case describes a simple technique for bailout with stent balloon rupture using conventional hardware, which may increase the probability of a successful outcome.